Severity and frequency of reactive and instrumental violent offending: divergent validity of subtypes of violence in an adult forensic sample - Tapscott, Jennifer L. (Criminal justice and behavior, 2012)
A common practice in forensic research is to distinguish between reactive and instrumental violence, but recent critics have asserted that these subtypes of violence are not orthogonal and that this distinction has outlived its usefulness. To test the validity of the reactive?instrumental distinction, the authors reviewed the official files of 71 violent male offenders to determine the frequency and severity of reactive and instrumental violent offending. Overall, 79% of violent offenses could be categorized as purely instrumental or purely reactive, and as hypothesized, reactive violent offenses were more severe than instrumental violent offenses. Both parametric and nonparametric correlation analyses indicated that the frequency of instrumental violent offending was negatively related to the frequency of reactive violent offending. These findings support the reactive?instrumental distinction. Implications pertaining to offender specialization, the general theory of crime, and specialized rehabilitation programs are discussed.